Development Of Integrated Portal (IP) As An E-tool For The Enhancement Of Job Marketability - SalakoTaofiqat Adebosola; ZulHilmi Bin Abdullah; Khairi Abdul Rahim; Shaharudin Ismail (American Research Institute for Policy Development, 2024)
This paper analyses the need to develop an Integrated Portal (IP) to facilitate job market ability and lists its components. The IP will be in form of a website which allows known stakeholders to make use of it. The stakeholders are identified in this paper and the features of the Integrated Portal are also briefly explained. It also goes further to explain the benefits and some basic requirements needed for the IP. The e portfolio is used as the main system while other small systems are linked to it.